Komunikasi Antarbudaya dalam Film Victoria and Abdul - Eka Saputra (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2020)
The film "Victoria & Abdul" is a film with a docudrama genre that tells the true story of Queen Victoria who lived in 1875 and Abdul, a servant of Queen Victoria who came from India. In this study, the writer wants to analyze the content of the film from the point of view of the intercultural communication. The forms of intercultural communication proposed by De Vito. Of the eight forms of De Vito's intercultural communication, this is the main study in this study. There are only four forms that will be the limitation in this analysis, there is (1) communication between different religions, (2) communication between different cultures, (3) communication between subcultures with dominant cultures, (4) communication between different gender and (5) communication between different ethnic groups. The methodology used to obtain the results of this study uses the descriptive analysis method by Tzvetan Todorov. According to Todorov, every film has a story and plot. The story is the story of the film itself, and it is an idea, not a physical one, while the plot is the plot that determines how the story will be run, and this requires physical activity.